The synergistic role of the immune system and stem cells in dental tissue regeneration - Darmadi, Eveline Yulia; Fauziah, Yessy Andriani (Conservative Dentistry Journal, 2025)
Background: Dental conservation focuses on maintaining natural teeth structure, function, and aesthetics using various techniques. Recent developments in regenerative dentistry highlight the immune system's and stem cells' crucial roles in regenerating dental tissues. The immune system is key in preserving oral health and supporting healing after treatment. Incorporating stem cell therapy presents a promising strategy for restoring damaged tissues, potentially enhancing the effectiveness of dental conservation. Purpose: This review explores the growing potential of immune system modulation and stem cell therapy in promoting tissue regeneration and optimizing clinical outcomes in dental conservation. It aims to summarize recent research while examining this evolving field's benefits, challenges, and future prospects. Reviews: Research indicates that the immune system's inflammatory response plays a dual role as it is crucial for wound healing but can lead to tissue damage if not regulated. Recent studies emphasize the importance of balancing pro-inflammatory and anti-inflammatory mechanisms to optimize tissue regeneration. Stem cells show promising potential in regenerating dentin, pulp, and periodontal tissues. Integrating stem cell therapy with immune modulation may further enhance regenerative outcomes. However, translating these approaches into clinical practice remains challenging due to concerns regarding safety, effectiveness, and ethical considerations. Conclusion: Regulating the immune system and integrating stem cell therapy offer promising advancements in dental conservation. Effectively utilizing these biological mechanisms can enhance tissue regeneration and improve treatment success. Future studies should aim to refine protocols, ensure long-term safety, and overcome practical barriers to fully incorporate these innovations into everyday clinical practice.